2021
DOI: 10.3390/cancers13205225
|View full text |Cite
|
Sign up to set email alerts
|

Currently Used Laboratory Methodologies for Assays Detecting PD-1, PD-L1, PD-L2 and Soluble PD-L1 in Patients with Metastatic Breast Cancer

Abstract: Approximately 20% of breast cancer (BC) patients suffer from distant metastasis. The incidence and prevalence rates of metastatic BC have increased annually. Immune checkpoint inhibitors are an emerging area of treatment, especially for metastatic patients with poor outcomes. Several antibody drugs have been developed and approved for companion testing of the programmed death protine-1 (PD-1) axis. We reviewed currently used laboratory methodologies for assays determining PD-1 axis to provide a comprehensive u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 116 publications
(163 reference statements)
0
10
0
Order By: Relevance
“…Currently, there are diverse developed PD-L1 assays to evaluate PD-L1 expression: SP142, SP263, 28-82, 22C3, E1L3N, 73-10, E1J2J, 5H1, 4059 and 9A11, among others [ 6 , 22 , 26 , 27 , 28 ]. The IHC assays that are most frequently used to determine the expression level of PD-L1 are PD-L1 IHC 22C3pharmDx Assay (PD-L1 22C3, DAKO) and SP142 Assay (PD-L1 SP142, VENTANA) ( Table 2 ) [ 3 , 5 , 6 , 28 , 29 ]. Normally, the approval of immunotherapy drugs is often linked to a certain PD-L1 IHC assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are diverse developed PD-L1 assays to evaluate PD-L1 expression: SP142, SP263, 28-82, 22C3, E1L3N, 73-10, E1J2J, 5H1, 4059 and 9A11, among others [ 6 , 22 , 26 , 27 , 28 ]. The IHC assays that are most frequently used to determine the expression level of PD-L1 are PD-L1 IHC 22C3pharmDx Assay (PD-L1 22C3, DAKO) and SP142 Assay (PD-L1 SP142, VENTANA) ( Table 2 ) [ 3 , 5 , 6 , 28 , 29 ]. Normally, the approval of immunotherapy drugs is often linked to a certain PD-L1 IHC assay.…”
Section: Resultsmentioning
confidence: 99%
“…The PD-L1 immunohistochemistry (IHC) biomarker landscape is complex due to the heterogeneity of IHC assays, with diverse scoring algorithms approved for different scenarios and tumor indications [ 3 ]. Currently, the most commonly used anti-PD-L1 antibody clones are 22C3, SP142, SP263, 28-8, E1L3N and 73-10 [ 4 , 5 , 6 ]. Insufficient studies have evaluated the PD-L1 expression in tumor and immune cells in BC, and preliminary data are divergent with still great variability in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In determining the impact of pro-inflammatory cytokines on the expression of PD-L1 and PD-L2 in TNBC cells, we have analyzed the effects of TNFα, IL-1β and IFNγ, each alone and in all possible combinations, in pairs and as a triplet stimulation (cytokine concentrations were selected as described in Section 2 ). Moreover, in view of the fact that both PD-L1 and PD-L2 were found to be expressed by breast tumor cells in patients and to be associated with each other [ 50 , 51 , 52 , 53 , 77 ], we have also analyzed the proportions of TNBC cells that co-expressed PD-L1 and PD-L2 together.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have investigated the impact of the pro-inflammatory cytokines on PD-L2 expression by the cancer cells. Emerging findings have recently demonstrated that PD-L2, the other PD-1 ligand, is expressed by cancer cells and is connected to poor prognosis, including in breast cancer, presumably by its ability to down-regulate immune activities [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no standardized method for PD-L1 assessment. SP142, SP263, 28-82, 22C3, E1L3N, 73–10, E1J2J, 5H1, 4059, and 9A11 are some assays among others [ 43 ]; of these, the PD-L1 IHC 22C3pharmDx Assay (PD-L1 22C3, DAKO) and SP142 Assay (PD-L1 SP142, VENTANA) are used most often [ 47 , 48 , 49 , 50 ]. Commonly, the approval of immunotherapy drugs joins with a predetermined IHC assay.…”
Section: Introductionmentioning
confidence: 99%